Integrated taxonomy to advance species delimitation of the Anopheles maculipennis complex - Mattia Calzolari; Nicolò Bellin; Michele Dottori; Deborah Torri; Marco Di Luca; Valeria Rossi; Giulia Magoga; Matteo Montagna (Scientific Reports)
Abstract The Anopheles maculipennis complex consists of several mosquito species, including some primary malaria vectors. Therefore, the presence of a species in a particular area significantly affects public health. In this study, 1252 mosquitoes were collected in northern Italy, representing four identified species of the Anopheles maculipennis complex (Anopheles daciae sp. inq., Anopheles maculipennis s. s., Anopheles atroparvus and Anopheles melanoon). The sequences of two DNA markers, mitochondrial cytochrome c oxidase I (COI) and nuclear internal transcribed spacer 2 (ITS2), were generated. DNA-based species delimitation analyses were performed, incorporating public sequences, with distance-based and coalescent tree-based methods to confirm the actual species boundaries within the complex. While some morphospecies were unequivocally delimited by all methods and markers, COI analysis splitted An. maculipennis s. s. into two well-supported groups. However, molecular delimitation failed in recognizing An. daciae sp. inq. and An. messeae as two separate evolutionary entities. Species delimitation was further tested with a morphometric approach, which clearly differentiated species collected in the survey area. These findings underscore how challenging the characterization of the taxonomy of the complex is, providing evidence of potential introgression events in An. maculipennis s. s. and suggesting the need for robust evidence to support An. daciae sp. inq. and An. messeae as distinct species.